2002
DOI: 10.1051/0004-6361:20020856
|View full text |Cite
|
Sign up to set email alerts
|

Time delay and lens redshift for the doubly imaged BAL quasar SBS 1520+530

Abstract: Abstract. We present optical R-band light curves of the gravitationally lensed quasar SBS 1520+530 derived from data obtained at the Nordic Optical Telescope. A time delay of 130 ± 3 days (1σ) is determined from the light curves. In addition, spectra of SBS 1520+530 obtained at the Keck Observatory are spatially deconvolved in order to extract the spectrum of the faint lensing galaxy, free of any contamination by the light from the bright quasar images. This spectrum indicates a lens redshift z = 0.717, in agr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
3
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 12 publications
9
69
3
2
Order By: Relevance
“…Figure 22 shows the result of the simultaneous modeling of 5 systems with time delays obtained at the NOT. These are RX J0911+055 (Hjorth et al 2002), SBS B1520+530, (Burud et al 2002b), B1600+434 (Burud et al 2000) and J0951+263 (Jakobsson et al 2005) and the time delay of SDSS J1206+4332 reported in this paper. On the histogram the results of our simultaneous modeling of the 5 QSOs are presented.…”
Section: Simultanous Modelingsupporting
confidence: 54%
“…Figure 22 shows the result of the simultaneous modeling of 5 systems with time delays obtained at the NOT. These are RX J0911+055 (Hjorth et al 2002), SBS B1520+530, (Burud et al 2002b), B1600+434 (Burud et al 2000) and J0951+263 (Jakobsson et al 2005) and the time delay of SDSS J1206+4332 reported in this paper. On the histogram the results of our simultaneous modeling of the 5 QSOs are presented.…”
Section: Simultanous Modelingsupporting
confidence: 54%
“…-SBS 1520+530: two data sets exist for this doubly lensed quasar: the set made available by Burud et al (2002b) and the one published by Gaynullina et al (2005a). Burud et al (2002c) were the first to publish a time delay for this system Δt AB = 128 ± 3 days, where A is the leading image, or Δt AB = 130 ± 3 days when using the iterative version of the method . Gaynullina et al (2005b) used an independent data set and found four possible time delays, of which the one with the largest statistical weight, Δt AB = 130.5 ± 2.9, is perfectly consistent with the previously published time delays.…”
Section: Application To 11 Lensed Quasarsmentioning
confidence: 99%
“…∆t BD ? ∆t CD 28.6 ± 9.4 JVAS B1422+231 (Patnaik & Narasimha 2001) 15 GHz ∆t AB −1.5 ± 1.4 1.1 ± 2.1 ∆t AC 7.6 ± 2.5 −0.4 ± 3.0 ∆t BC 8.2 ± 2.0 −0.4 ± 3.2 SBS 1520+530 (Burud et al 2002b) R ∆t AB 130 ± 3 124.2 ± 8.1 CLASS B1600+434 (Burud et al 2000) I ∆t AB 51 ± 4 (95% CI) ? CLASS B1600+434 (Koopmans et al 2000) 8.5 GHz ∆t AB 47 +5 77.6 ± 3.5 ∆t CD 41.3 ± 1.6 SDSS J1650+4251 (Vuissoz et al 2007) R ∆t AB 49.5 ± 1.9 59.2 ± 15.9 PKS 1830−211 (Lovell et al 1998) 8.6 GHz ∆t AB 26 +4…”
Section: H 0 From Pixellated Modeling Of Ten Gravitational Lensesmentioning
confidence: 99%